A Neural Network based Frequency-domain Design Method for the Optimal Fractional Order PIλDμ Controller. (June 2020) - Zheng, Weijia; Luo, Ying; Chen, YangQuan
Abstract: A neural network (NN) based frequency-domain design method for the optimal PI λ D μ controller is proposed in this paper, dividing the tuning process of the PI λ D μ controller into two steps: the fractional orders of the controller are estimated by the NN based estimation models, and other controller parameters are calculated analytically using a modified frequency-domain method. A practical application of the proposed method on the permanent magnet synchronous motor (PMSM) speed control problem is studied. Motor speed control simulation is performed to verify the gain robustness, step response performance and anti-load disturbance performance of the obtained control system. Comparison with the typical frequency-domain method is performed and then the advantage of the proposed method is demonstrated.